Research on the Effect of Curing Temperature, Steel Fiber, and Admixture Content on Concrete Performance Based on Orthogonal Test in Cold Region - Z. G. Zhu; K. P. Hou; H. F. Sun; Y. Cheng; B. J. Yang; W. Sun (Advances in Materials Science and Engineering)
Cold region covers over 50% all over the world. As an indispensable part of the project, concrete is greatly affected by temperature during the curing process. In this paper, through the orthogonal experiment design, we studied the mixing temperature, steel fiber, and water reducing agent dosage on concrete mixture slump; the influence of curing temperature, steel fiber, water reducing agent, and accelerating agent content on compressive strength of concrete; and the influence of the final microstructure by scanning electron microscopy (28-day concrete, analysis of the degree of hydration reaction). The results show that the slump of concrete increases with the amount of water reducing agent. Mixing temperature and steel fiber content have little effect on the workability of the mixture. Curing temperature has a significant effect on the growth of concrete compressive strength. The higher curing temperature is within 0∼20°C, the faster the growth of concrete strength is. The longer the age of concrete, the greater the compressive strength. The content of water reducing agent and accelerating agent only has a significant effect on the early strength of concrete, while the content of steel fiber has a great effect on the late strength of concrete. Curing temperature affects the degree of hydration reaction of concrete. The higher the curing temperature, the more the cementing substances produced by hydration reaction of concrete, the higher the degree of hydration reaction, and the higher the strength of concrete. The research results are helpful to improve the mine support operation in high-cold and high-temperature difference area.